Annual Plan 1993-94 Orissa Vol. II - Planning Commission (Planning Commission, 1992)
Progress of Expenditure during the Annual Plans and outlay for the Annual Plan, 1993-94. Physical Target and Achievements during the Annual Plans, 1991-92 1992-93 and Target for the Annual Plan, 1993-94. , A Proposals for spill over and on-going programmes/projects , Proposals for maximising benefits of completed programmes/projects , Proposals for programmes/projects—New Schemes , Summary Statement , Externally Aided Projects , District Plans , District-wise Break up—Expenditure for 1991-92 , District-wise Break up—outlay for 8th Plan , District-wise Break up—Anticipated Expenditure for 1992-93 , District-wise Break up—outlay for 1993-94 , Centrally Sponsored Schemes , Minimum Needs Programme—outlay and expenditure
Annual Plan 1993-94 Orissa Vol. II
Government of Orissa